Chiari malformation with concurrent papilledema: a patient-level meta-analysis of case reports and case series - Alejandro Pando; Daniel J. Valdivia; Daniel A. Brenner; Mohammed Ali Alvi; Hai Sun; James K. Liu; Ira Goldstein (Egyptian Journal of Neurosurgery)
Abstract Background Chiari I malformation, characterized by the displacement of cerebellar tonsils, and Chiari 1.5, involving cerebellar tonsils and brainstem displacement, share symptoms with Idiopathic Intracranial Hypertension, including headache, paresthesia, vision issues, shoulder/arm pain, diplopia, numbness, and motor weakness. Historically, papilledema marked IIH, but there are reports of papilledema in patients with Chiari I/1.5, leading to uncertainty about the most effective treatment strategies. We aim to address this gap by summarizing all reported cases of Chiari I/1.5 with papilledema. Methods Three primary electronic databases (PubMed, EMBASE, and SCOPUS) were screened to identify case reports and case series of patients with Chiari malformation presenting with papilledema. All variables such as year and region of study, age, sex, symptoms, diagnostic information, treatment details, and follow-up duration, were recorded and analyzed. Study quality for each study included was assessed according to four scales: selection, ascertainment, causality, and reporting. Results 27 patients from 21 studies were included. Symptoms included headache (76.4%), decreased visual acuity (70.8%), and visual field loss (29.2%). 44.4% had lumbar punctures, and 40.7% received medical management. Of those managed medically, 41.7% fully recovered. Notably, none of 21 patients who underwent surgical decompression without improvement had prior lumbar puncture (0% vs. 64.3%, n = 9; p = 0.003) or medical management (0% vs. 57.1%, n = 8; p = 0.011) compared to those with symptom improvement. Conclusion Chiari malformation with papilledema exhibits varied symptoms. Medical management should be considered initially, offering standalone effectiveness and potential improvement for subsequent decompression if medication alone does not lead to recovery.